2013
DOI: 10.1177/1470320313477174
|View full text |Cite
|
Sign up to set email alerts
|

The balance between human maternal plasma angiotensin II and angiotensin 1-7 levels in early gestation pregnancy is influenced by fetal sex

Abstract: Hypothesis: There are fetal sex-associated differences in the circulating maternal renin-angiotensin system (RAS) in early pregnancy. Methods: Plasma prorenin, angiotensin (Ang) II, Ang 1-7 and angiotensin-converting enzyme (ACE) concentrations were measured at 15 weeks' gestation in 131 women with uncomplicated pregnancies from the Adelaide SCOPE cohort. Uterine and umbilical artery Doppler sonography was performed at 20 weeks' gestation. Results: At 15 weeks, women bearing female fetuses had higher maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…Instead of postnatal vasoconstriction, peripheral dilation persists, driven by a number of mechanisms, one of which may be H 2 S. This hypothesis of persistent dilatory status following preterm birth is also supported by a growing body of work on the renin angiotensin system. Studies in a range of species, including humans, suggest that the balance of vasoactive renin angiotensin system peptides and their receptors favors vasodilatation during gestation and fetal life, particularly in males, and that this rapidly switches following birth—similar to the profile observed in the present study, with vasodilatation favored prenatally, and rapidly downregulated postnatally in term neonates. This, however, fails in preterm neonates who are unprepared for the extrauterine environment.…”
Section: Discussionsupporting
confidence: 78%
“…Instead of postnatal vasoconstriction, peripheral dilation persists, driven by a number of mechanisms, one of which may be H 2 S. This hypothesis of persistent dilatory status following preterm birth is also supported by a growing body of work on the renin angiotensin system. Studies in a range of species, including humans, suggest that the balance of vasoactive renin angiotensin system peptides and their receptors favors vasodilatation during gestation and fetal life, particularly in males, and that this rapidly switches following birth—similar to the profile observed in the present study, with vasodilatation favored prenatally, and rapidly downregulated postnatally in term neonates. This, however, fails in preterm neonates who are unprepared for the extrauterine environment.…”
Section: Discussionsupporting
confidence: 78%
“…However, it has been shown that male fetuses born at 24–28 weeks of gestation have more peripheral vasodilatation compared to female fetuses [ 44 ]. Furthermore, pregnant women carrying male fetuses are reported to have higher angiotensin (Ang) 1–7 to Ang II ratio in the second trimester [ 45 ]. As Ang II is a potent vasoconstrictor and Ang 1–7 is a known vasodilator, relative vasodilatation of placental vessels could be responsible for lower UA PI, RI, and S/D ratio observed in male fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Of these peptides, ANG II and ANG (1-7) have been most studied in human pregnancy. At 15 wk gestation, ANG II levels are lower and the ANG (1-7)/ANG II ratio higher in women carrying male fetuses than in women carrying female fetuses (75). Baker et al (4) found that plasma ANG II levels were elevated by the second trimester.…”
Section: Changes In Components Of the Circulating Raas In Normal Pregmentioning
confidence: 99%